2013
DOI: 10.1088/1478-3975/10/5/056010
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine index as a marker of the procoagulant phenotype of acute myelogenous leukemia cells

Abstract: Summary Background Patients with Acute Myelogenous Leukemia (AML) are at risk for thrombotic complications. Risk to develop thrombosis is closely tied to leukemia subtype, and studies have shown an association between leukocytosis and thrombosis in AML M3. Objective To investigate the relative roles of cell count and the surface expression of tissue factor (TF) and phosphatidylserine (PS) in the procoagulant phenotype of AML cell lines. Methods and Results We evaluated the relative roles of cell count and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The effect of ATRA on TF protein and activity is delayed with respect to its rapid effect on TF mRNA and is only evident at 24 h. Even then, significant procoagulant activity is still detected and this information is quite relevant in the context of reducing hemorrhagic complication in the early treatment phase [ 57 ]. In agreement with previous reports [ 58 , 59 ], we found with the CAT assay that cells and microparticles bring both TF and an appropriate surface, since a substantial inhibition was obtained in presence of anti-TF antibody and since we did not add extra phospholipids. Of note, inhibition of thrombin generation as assessed with the CAT assay appeared to be less than that measured with the artificial Xa generation assay.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of ATRA on TF protein and activity is delayed with respect to its rapid effect on TF mRNA and is only evident at 24 h. Even then, significant procoagulant activity is still detected and this information is quite relevant in the context of reducing hemorrhagic complication in the early treatment phase [ 57 ]. In agreement with previous reports [ 58 , 59 ], we found with the CAT assay that cells and microparticles bring both TF and an appropriate surface, since a substantial inhibition was obtained in presence of anti-TF antibody and since we did not add extra phospholipids. Of note, inhibition of thrombin generation as assessed with the CAT assay appeared to be less than that measured with the artificial Xa generation assay.…”
Section: Discussionsupporting
confidence: 93%
“…In support of this, in vitro studies have shown heterogeneity in cancer cell surface expression of TF and PS, both of which are critical to determining the procoagulant phenotype of cancer cells. As such, the utility of implementing CTC analysis as a means to rationally base thrombosis prophylaxis may hinge upon determining critical features of CTCs in addition to CTC counts as a marker for risk to develop thrombosis (114). …”
Section: Clinical Considerations For the Procoagulant Phenotype Ofmentioning
confidence: 99%
“…Exposure of PS on the outer leaflet and microparticles (MPs) are found in the process of apoptosis ( 12 , 13 ). In addition, PS exposure on the outer membrane surface can function as a docking site for various coagulation proteins, including factor (F)VII, FIX, FV, FVIII, FX and prothrombin, and promote the formation of thrombin ( 14 , 15 ). As a primary cellular initiator of blood coagulation via interaction with coagulation FVII, tissue factor (TF) is generally quiescent unless it resides on a cell membrane containing PS ( 16 ).…”
Section: Introductionmentioning
confidence: 99%